Right of thirst : a novel - Huyler, Frank, 1964- (New York : Harper Perennial, 2009)
Volunteering to assist earthquake relief efforts in an impoverished Islamic country after the shattering death of his wife, successful cardiologist Charles Anderson encounters life-threatening hostilities when the refugees he expects do not appear and the area where he is stationed comes under fire.
Keywords: Physicians -- Fiction; Humanitarian assistance -- Fiction; Medical novels